2018
DOI: 10.1371/journal.pone.0199807
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative cytokine profile during lung surgery predicts patients at risk for postoperative complications—A prospective, clinical study

Abstract: BackgroundPostoperative complications after lung surgery are frequent, having a detrimental effect on patients’ further course. Complications may lead to an increased length of hospital stay and cause additional costs. Several risk factors have been identified but it is still difficult to predict contemporary which patients are at risk. We hypothesized that patients who show an increased inflammatory response at the time of wound closure and 24 hours after surgery are at risk of postoperative complications wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 23 publications
7
27
1
2
Order By: Relevance
“…Multiple studies have demonstrated that smoking increases the likelihood pulmonary complications ( Bluman et al, 1998 ; Kaufmann et al, 2018 ). However, our results showed no difference between non-smokers and smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that smoking increases the likelihood pulmonary complications ( Bluman et al, 1998 ; Kaufmann et al, 2018 ). However, our results showed no difference between non-smokers and smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory response and immune system dysfunction have drawn an increasing amount of attention from researchers as important prognostic indicators (2,3). In critically ill patients, dysfunction of the immune system is characterized by abnormal function and increased expression of pro-inflammatory cytokines, damageassociated molecular patterns (DAMPs) and acutephase proteins (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Patients undergoing thoracotomy have been reported to show a profound interleukin (IL)‐6, IL‐8, IL‐10 and tumor necrosis factor (TNF)‐α production in serum compared to that in patients undergoing VATS lung resection, which has been shown to affect further proinflammatory properties and host defense against infections 4, 5 . In addition, IL‐6 and IL‐10 plasma concentrations have been shown to be elevated at the time of wound closure and on the first postoperative day, predicting a significant probability of postoperative complications and emerging as a risk factor in these patients 6 . Furthermore, there are emerging evidences to suggest that there is a relationship between lymphocyte, natural killer (NK) cell count, function, signaling and surgical approach.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 In addition, IL-6 and IL-10 plasma concentrations have been shown to be elevated at the time of wound closure and on the first postoperative day, predicting a significant probability of postoperative complications and emerging as a risk factor in these patients. 6 Furthermore, there are emerging evidences to suggest that there is a relationship between lymphocyte, natural killer (NK) cell count, function, signaling and surgical approach. Thoracotomy has previously been reported to cause a significant reduction in CD4 + T cell count and a prolonged NK cell suppression when compared with VATS resection.…”
Section: Introductionmentioning
confidence: 99%